Open In App
Related Articles

Aptitude | Algebra | Question 5

Improve
Improve
Improve
Like Article
Like
Save Article
Save
Report issue
Report

Solve for x in the equation: log(2x – 1) + log(3) = log(x + 5) 

(A)

x = -1/3 

(B)

x = 1/3 

(C)

x = 5/3 

(D)

x = 8/5



Answer: (D)

Explanation:

Using the property of logarithms that states log(a) + log(b) = log(ab), we can simplify the equation as log(3(2x – 1)) = log(x + 5). Therefore, we have 6x – 3 = x + 5. Simplifying, we get 5x = 8, which gives us x = 8/5. Hence, the answer is D) x = 8/5.



Quiz of this Question
Please comment below if you find anything wrong in the above post

Last Updated : 28 Jun, 2021
Like Article
Save Article
Previous
Next
Share your thoughts in the comments
Similar Reads